Interaction between gender and age on the methylation levels of KLF14 promoter - Chiung-Hung Chiang; Yen-Chung Chen; Oswald Ndi Nfor; Wen-Yu Lu; Yung-Po Liaw (Scientific Reports)
Abstract This study investigated the relationship between age, sex, and methylation levels of the Krüppel-like factor 14 (KLF14) promoter. Utilizing data from the Taiwan Biobank (TWB), established in 2005, we analyzed a cohort of 1,141 participants. DNA methylation analyses were conducted by Health GeneTech Corp., commissioned by TWB. Methylation levels of the KLF14 promoter were determined by averaging the values of 10 CpG sites: cg09823095, cg25109431, cg21449170, cg05651960, cg18751682, cg08097417, cg07955995, cg22285878, cg21520933, and cg06533629. Participants were divided into four age groups (30–40, 40–50, 50–60, and 60–70 years). Multiple linear regression analyses were performed to assess the impact of age and sex on KLF14 promoter methylation and to evaluate the interaction between these variables. Our findings revealed that men exhibited higher KLF14 promoter methylation levels, with a significant age-dependent increase. Notably, in participants aged over 50, KLF14 methylation levels were substantially higher in men compared to women (β = 0.00336, P = 0.0108 for the 50–60 age group; β = 0.00472, P = 0.0238 for the 60–70 age group). Our study reveals a sex-specific increase in KLF14 promoter methylation among men over 50, with no significant differences observed in individuals younger than 50. This finding suggests that age and sex may play a crucial role in the epigenetic regulation of KLF14.